2014
DOI: 10.1088/0031-9155/60/2/595
|View full text |Cite
|
Sign up to set email alerts
|

Phantom based evaluation of CT to CBCT image registration for proton therapy dose recalculation

Abstract: The ability to perform dose recalculation on the anatomy of the day is important in the context of adaptive proton therapy. The objective of this study was to investigate the use of deformable image registration (DIR) and cone beam CT (CBCT) imaging to generate the daily stopping power distribution of the patient. We investigated the deformation of the planning CT scan (pCT) onto daily CBCT images to generate a virtual CT (vCT) using a deformable phantom designed for the head and neck (H & N) region. The phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…18,20 However, we believe it necessary for this to be independently conducted since the residual HU errors after the scatter correction would have different effects on proton dose calculations compared to photon cases. Moreover, this validation cannot be done in real patient images, as there would be no ground truth of CT ref to compare with daily CBCT images unless CT and CBCT images are acquired at the same patient setup as pointed out by Landry et al 12 Recently, Landry et al 12,13 investigated the feasibility of proton dose calculations on a virtual CT image using deformable image registration between plan CT and daily CBCT images. Even though they demonstrated a promising WEPL error (2% error of the proton range), they encountered residual DIR errors of 2-3 mm which potentially degrade the effectiveness T III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 However, we believe it necessary for this to be independently conducted since the residual HU errors after the scatter correction would have different effects on proton dose calculations compared to photon cases. Moreover, this validation cannot be done in real patient images, as there would be no ground truth of CT ref to compare with daily CBCT images unless CT and CBCT images are acquired at the same patient setup as pointed out by Landry et al 12 Recently, Landry et al 12,13 investigated the feasibility of proton dose calculations on a virtual CT image using deformable image registration between plan CT and daily CBCT images. Even though they demonstrated a promising WEPL error (2% error of the proton range), they encountered residual DIR errors of 2-3 mm which potentially degrade the effectiveness T III.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies on CBCT imaging for APT. 12,13 It is expected that the HU accuracy of CBCT is more crucial in APT than it is in ART, because small HU differences may cause range errors and absolute dose errors, which will in turn lead to reduced integrity of the dose calculation. 14 To date, no study has demonstrated proton dose calculation or treatment planning on either raw or scatter-corrected CBCT images.…”
Section: Introductionmentioning
confidence: 99%
“…The method employed here was the same as in Landry et al 19 An automatic rigid translation registration was employed to align the CBCT and pCT, mimicking an online position correction protocol. Prior to rigid registration, the CBCT was cropped to eliminate the conical sections at the inferior end of the FOV.…”
Section: B Registrationmentioning
confidence: 99%
“…[13][14][15][16][17][18] A recent phantom study from our group suggested that the approach may provide stopping power distributions which are equivalent to those obtained by a planning CT with proton range differences below 2%. 19 However, that study was restricted to the evaluation of the stopping power distribution and did not explore the use of the vector field for contour propagation for a more profound analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Those that do are either limited to one room only with specific adaptations for a CT such as a “track” solution or cone‐beam CT (CBCT). An alternative to mobile helical CT scanners for image‐guided proton therapy is the gantry‐mounted cone‐beam CT (CBCT) 5, 6, 7, 8, 9. Gantry‐mounted CT systems may provide more convenience than mobile scanners.…”
Section: Introductionmentioning
confidence: 99%